Proses Morfologi Derivasional dan Infleksional dalam Bahasa Inggris dan Bahasa Arab: Derivational and Inflexional Morphology Process in English and Arabic - Ahmad Khoironi (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2021)
The main objective of this study was to compare word formation between English and Arabic. Each language that is analyzed will describe the formation of words according to inflectional and derivational processes. The Arabic data sources were taken from the durusul lughoh alḉarobiyyah book volumes 1-3 and the Koran, while the English data sources were obtained from the English dictionary. The research data is in the form of vocabulary in Arabic and English which changes shape according to inflectional and derivational processes. The results of this study indicate that there are similarities and differences in the morphological formation process of English and Arabic. The similarity is in the process of forming words in an inflectional way, which consists of affixation, non-affixation, and fixed form; while the difference is seen in the derivational process. Derivational in English includes affixation, non-affixation, and fixed form, while derivational in Arabic only occurs in the affixation process.